Comparative extraction of bromelain and bioactive peptides from pineapple byproducts by ultrasonic‐ and microwave‐assisted extractions. (23rd April 2021) - Mala, Thatchajaree; Sadiq, Muhammad Bilal; Anal, Anil Kumar
Abstract: Ultrasonic‐assisted extraction (UAE) and microwave‐assisted extraction (MAE) were used for the extraction of bioactive peptides from pineapple byproducts. Independent extraction parameters for UAE were ultrasonic amplitude (60–100%), extraction time (10–30 min), and solvent to material ratio (20–40 mL/g), whereas for MAE independent variables were microwave power (100–300 W), irradiation time (5–15 min), and feed to solvent ratio (1:8–1:12 g/mL). The optimized extraction conditions were 99.96%, 26.83 min, and 20.96 mL/g for UAE and 100 W, 8.99 min, and 1:8 g/mL for MAE. The optimized extraction resulted in total sugar, protein content, and proteolytic activity of 15.71 ± 0.03 mg/mL, 4.01 ± 0.04 mg/mL, and 196.46 ± 3.29 U/mL, respectively, whereas 33.87 ± 0.03 mg/mL, 2.50 ± 0.01 mg/mL, and 154.08 ± 1.49 U/mL for MAE, respectively. Scanning electron microscopy was used to observe the morphology of sample during extraction. Molecular weight determination showed that the major protein band in the extracts (UAE and MAE) was at ∼23 kDa which corresponded to bromelain. Furthermore, pineapple crown protein extract obtained by UAE showed high proteolytic activity (>80% relative). The present study indicated that bromelain and other bioactive peptides from pineapple byproducts have potential in food, feed, and pharmaceutical products development. Practical Applications: The conventional extraction techniques for bioactive compounds are time‐consuming and less efficient. The use of advance extraction techniques like microwave‐ and ultrasonication‐assisted extraction techniques can increase the extraction yield with better recovery of bioactive compounds. Pineapple byproducts are rich source of bioactive compounds and bromelain. The effective utilization of pineapple byproducts for the extraction of bromelain and other bioactive peptides will offer an effective solution for minimizing the organic waste and provide an efficient source of bioactive peptides for application in various food products. Abstract :